Molecular effects of Mastodynon: realities and prospects for cancer prevention - I. V. Vysotskaya; E. A. Kim; V. Yu. Kirsanov; S. B. Polikarpova; V. E. Ponomarev (Опухоли женской репродуктивной системы)
The article presents updated data concerning the molecular mechanisms of influence of the well-known in clinical practice drug Mastodynon. The paper provides evidence of a significant effect of the compounds containing in its composition on the cell lines of a number of malignant neoplasms: breast cancer, hepatocellular carcinoma, leukemia and others. The data obtained are extremely attractive in the perspective of using the drug as a preventive agent.